MASALAH CINA, MASALAH CINTA: POSISI ORANG TIONGHOA DALAM DI KAKI BUKIT CIBALAK KARYA AHMAD TOHARI - Christopher Woodrich (POETIKA, 2014)
e-width: 0px; "> For the duration of the New Order era (1966–98), the position of Chinese Indonesians was considereda problematic question: they were not “Pribumi” (native), but also not entirely Chinese. This “Chinese Problem”was discussed by a variety of speakers and writers, including several authors of literary works. In Di Kaki BukitCibalak (1977), Ahmad Tohari presents two ethnic Chinese characters, Nyonya Wibawa and Mulyani, the first asthe employer and the second as the lover of the main character, Pambudi. By applying Goldmann’s theory of geneticstructuralism, we show that through his depiction of the physical and behavioural aspects of the characters, Toharipromotes an assimilationist approach as the only possible solution to the Chinese problem (if it can be solved): thedichotomies between ethnic Chinese and Native Indonesians must be erased. However, Tohari continues to differentiatethe ethnic Chinese by positioning them as persons who must only act to support the welfare of the Pribumi.Keywords: “The Chinese Problem”, Ahmad Tohari, position of Chinese Indonesians, Di Kaki Bukit Cibalak